2023
DOI: 10.1002/aur.2926
|View full text |Cite
|
Sign up to set email alerts
|

Poor synchronization yet adequate tempo‐keeping in adults with autism

Abstract: Sensorimotor synchronization to external events is fundamental to social interactions. Adults with autism spectrum condition (ASC) have difficulty with synchronization, manifested in both social and non-social situations, such as paced finger-tapping tasks, where participants synchronize their taps to metronome beats. What limits ASC's synchronization is a matter of debate, especially whether it stems from reduced online correction of synchronization error (the "slow update" account) or from noisy internal rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 60 publications
2
13
1
Order By: Relevance
“…Our finding that timekeeper noise showed no effect on SPC skills is similar to findings of other studies that report that longer-term statistics are intact in individuals with ASC (Goris et al, 2022;Kasten et al, 2023;Lieder et al, 2019;Poole, Casassus, Gowen, Poliakoff, & Jones, 2022;Vishne et al, 2021). Other studies have suggested that timekeeping is impaired in ASC (Panagiotidi, Overton, & Stafford, 2017;Zhou et al, 2021).…”
Section: Timekeepingsupporting
confidence: 91%
See 3 more Smart Citations
“…Our finding that timekeeper noise showed no effect on SPC skills is similar to findings of other studies that report that longer-term statistics are intact in individuals with ASC (Goris et al, 2022;Kasten et al, 2023;Lieder et al, 2019;Poole, Casassus, Gowen, Poliakoff, & Jones, 2022;Vishne et al, 2021). Other studies have suggested that timekeeping is impaired in ASC (Panagiotidi, Overton, & Stafford, 2017;Zhou et al, 2021).…”
Section: Timekeepingsupporting
confidence: 91%
“…The significant focal exposure-outcome effect of motor error correction on SPC is consistent with Vishne et al (2021) who showed a dimensional relationship between communication in the AQ50 questionnaire and error correction as quantified with a similar computational model. Our study and that of Vishne and coauthors also are in line with ASC group studies (Kasten et al, 2023). Such studies have generally not quantified SPC, but it can be assumed that ASC individuals had clinical levels of SPC difficulties as they are required for an ASC diagnosis.…”
Section: Error Correction and Childhood Motor Symptoms In Spcsupporting
confidence: 88%
See 2 more Smart Citations
“…In our work we have found that when presenting rhythmic stimuli to individuals where the timing of stimulus onset is predictable, there is reduced phase locking of neuro-oscillations, as well as altered neural indices of predictive processing, in children with autism 26 . Taken together with evidence for impaired behavioral synchronization 27,28 and slower updating of motor and behavioral responses 29 when presented with rhythmic sensory stimulation, there is mounting evidence for altered neural synchronization with the environment as a possible mechanism contributing to autism. The critical role of neural entrainment in adaptive behavior and preliminary evidence of its impairment highlights the importance of understanding these neural functions in individuals with ASD and how they mediate interaction with the environment.…”
Section: The Effect Of Cns and Ans Rhythmic Activity In Perception An...mentioning
confidence: 99%